Identification, release and olfactory detection of bile salts in the intestinal fluid of the Senegalese sole (Solea senegalensis) - Velez, Zélia (2014)
Olfactory sensitivity to bile salts is wide-spread in teleosts; however, which bile salts are released in suYcient quantities to be detected is unclear. The current study identiWed bile salts in the intestinal and bile Xuids of Solea senegalensis by mass spectrometry–liquid chromatography and assessed their olfactory potency by the electro-olfactogram.